Investigation of opportunities the addition of canned watermelon pomace and watermelon juice produced from unmarketable watermelon in broiler quail ration - Çerçi, İbrahim Halil; Erocağı, Aydın; Karagözoğlu, Fatma (My University, 2020)
This study was conducted to evaluate the use of watermelon pomace and watermelon juice obtained from unmarketable watermelon in the diets of fattening quails. A total of 90 Japanese quails (Coturnix coturnix japonica) wereassigned to three groups (30 quails in each group), each comprising of 5 replicates each having 6 quails. One groupwas designated as control groups whereas other groups fed 5% watermelon pomace or watermelon juice on dry matter basis. All the diets were isonitrogenous and isocaloric formulated in order to meet the nutrient requirements ofquails outlined in NRC standards. Live weight was greater in quails fed watermelon pomace compared with controlgroup in first week only (P<0.05). Average daily gain of the quails was not different among the groups (P>0.05). Infirst week and overall period (1 to 4 wk), average daily feed intake (ADFI) was higher in control group than quailsfed watermelon juice which, in turn, was higher in comparison with those fed watermelon pomace (P<0.001). Insecond week, ADFI was greater in control group than other dietary treatments (P<0.01). The ADFI was higher inquails fed diet with watermelon juice than those fed diets containing watermelon pomace (P<0.05). Feed conversionratio (FCR) in the first week was lower quails fed watermelon pomace than control group (P<0.01). The FCR inoverall period improved in quails receiving diets with watermelon pomace compared with other dietary treatments(P<0.001). Nutrients digestibility and mortality rates almost were similar across the groups (P>0.05). In conclusion,it was observed that watermelon pomace can be used in quail diets having additional growth enhancer properties.
Keywords: Beslenme ve Diyetetik; Ziraat Mühendisliği; Gıda Bilimi ve Teknolojisi; Bitki Bilimleri